The production and detoxification of a potent cytotoxin, nitric oxide, by pathogenic enteric bacteria. (21st November 2011) - Arkenberg, Anke; Runkel, Sebastian; Richardson, David J.; Rowley, Gary
Abstract : The nitrogen cycle is based on several redox reactions that are mainly accomplished by prokaryotic organisms, some archaea and a few eukaryotes, which use these reactions for assimilatory, dissimilatory or respiratory purposes. One group is the Enterobacteriaceae family of Gammaproteobacteria, which have their natural habitats in soil, marine environments or the intestines of humans and other warm-blooded animals. Some of the genera are pathogenic and usually associated with intestinal infections. Our body possesses several physical and chemical defence mechanisms to prevent pathogenic enteric bacteria from invading the gastrointestinal tract. One response of the innate immune system is to activate macrophages, which produce the potent cytotoxin nitric oxide (NO). However, some pathogens have evolved the ability to detoxify NO to less toxic compounds, such as the neuropharmacological agent and greenhouse gas nitrous oxide (N2 O), which enables them to overcome the host's attack. The same mechanisms may be used by bacteria producing NO endogenously as a by-product of anaerobic nitrate respiration. In the present review, we provide a brief introduction into the NO detoxification mechanisms of two members of the Enterobacteriaceae family: Escherichia coli and Salmonella enterica serovar Typhimurium. These are discussed as comparative non-pathogenic and pathogenic model systems in order to investigate the importance of detoxifying NO and producing N2 O for the pathogenicity of enteric bacteria.